2011
DOI: 10.1016/j.jvs.2010.10.135
|View full text |Cite
|
Sign up to set email alerts
|

Open surgery versus endovascular repair of ruptured thoracic aortic aneurysms

Abstract: Endovascular repair of rDTAA is associated with a lower risk of a composite of death, stroke, and paraplegia, compared with traditional open surgery. In rDTAA patients, endovascular management appears the preferred treatment when this method is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 39 publications
2
88
0
10
Order By: Relevance
“…Another recent multicenter, retrospective review of 69 patients with ruptured DTAA published by the same authors demonstrated a composite outcome of death, stroke, or permanent paraplegia in 36.2%. 127 These results were confirmed by a larger study, including data from the US Nationwide Inpatient Sample data on 559 patients with ruptured DTAA, with a reported mortality rate of 28.6%. 128 These data confirm that OR for ruptured DTAA is associated with high mortality and morbidity.…”
Section: Iib B 104mentioning
confidence: 52%
See 2 more Smart Citations
“…Another recent multicenter, retrospective review of 69 patients with ruptured DTAA published by the same authors demonstrated a composite outcome of death, stroke, or permanent paraplegia in 36.2%. 127 These results were confirmed by a larger study, including data from the US Nationwide Inpatient Sample data on 559 patients with ruptured DTAA, with a reported mortality rate of 28.6%. 128 These data confirm that OR for ruptured DTAA is associated with high mortality and morbidity.…”
Section: Iib B 104mentioning
confidence: 52%
“…LSA revascularisation was not performed in most of these cases. 127,128 Comprehensive data regarding the rationale for LSA coverage without revascularisation are unavailable. In one study, subclavian artery bypass was performed in half of the cases (10/19 covered) before TEVAR.…”
Section: Iib B 104mentioning
confidence: 99%
See 1 more Smart Citation
“…Open surgical repair of rDTAA presents very high mortality rates and is only feasible in referral centers. Mortality rates for open surgery vary from 30% to 60% depending on the series (Jonker et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of neurological complications may increase after endovascular repair of rDTAA, although it is still lower than that of open repair. The incidence of paraplegia and stroke after conventional surgical treatment of rDTAA may be as high as 12.5% and 25% (Jonker et al, 2011;Barbato et al, 2007), providing even greater support for endovascular treatment of rDTAA. Although TEVAR is currently the most appropriate approach for the management of this often-fatal lesion, endovascular repair of rDTAA is still associated with considerable rates of neurological complications and procedure-related complications such as endoleak.…”
Section: Discussionmentioning
confidence: 99%